Numerical formulation for solving soil tool interaction problem involving large deformation - Renon, Nicolas; Montmitonnet, Pierre; Laborde, Patrick (Engineering computations, 2005)
Purpose - The aim of this work is to provide a global 3D finite element (FE) model devoted to the modelling of superficial soil ploughing in the large deformation range and for a vast class of soil treatment tools. Design methodology approach - We introduced soil constitutive equation in a FE software initially designed for the metal forming. We performed the numerical integration of the non-linear ploughing problem. Non-linearities encountered by the problem can be summed up: as soil constitutive equation (idealized with non-associated compressible plastic law), unilateral frictional contact conditions (with a rigid body), geometrical non-linearities (the ploughing tool) and large deformation range. To handle such difficulties we performed several numerical methods as implicit temporal scheme, Newton-Raphson, non-symmetric iterative solver, as well as proper approximation on stress and strain measures. Findings - Main results deal with the validation of the integration of the non-linear constitutive equation in the code and a parametric study of the ploughing process. The influence of tool geometric parameters on the soil deformation modes and on the force experienced on the tools had been point out. As well, the influence of soil characteristics as compressibility had been analyzed. Research limitations implications - This research is devoted to perform a numerical model applicable for a large range of soil treatment tools and for a large class of soil. However, taking into account all kind of soil is utopist. So limitations met are essentially related to the limit of the accuracy of the elasto-plastic idealization for the soil. Practical implications - In practice the numerical model exposed in the paper can clearly help to improve and optimize any process involving superficial soil submitted to the mechanical action of a rigid body. Originality value - The original value of the paper is to provide a global and an applicable numerical model able to take into account the main topics related to the ploughing of superficial soils. Industrials in geotechnics, in agriculture or in military purposes can benefit in using such numerical model.